A comparation of three different anti-VEGF drugs in development of persistent avascular retina in premature children - Ayşe Cengiz Ünal; Melih Akıdan; Muhammet Kazım Erol (Scientific Reports)
Abstract Our current prospective cross-sectional study aimed to investigate the effect of anti-vascular endothelial growth factor (VEGF) drugs used in the treatment of retinopathy of prematurity on retinal maturation and persistent avascular retina (PAR). Retinal imaging was performed with Optos confocal laser ophthalmoscopy for 100 patients aged 4 to 8 years who were screened and treated for retinopathy of prematurity (ROP) during the neonatal period. The ROP examination findings (stage and zone) and treatment history (age in weeks at time of treatment and anti-VEGF drug used) from the neonatal period were reviewed. Retinal vascularization was assessed in fundus images using the green filter on the Optos device and the presence of PAR was evaluated by two investigators. Relationships between the rate of PAR, age in weeks at time of treatment, and type of anti-VEGF drug used were analyzed statistically. The study included 196 eyes of 100 patients. Sixty-four eyes were analyzed in Group 1 (no ROP), 23 eyes in Group 2 (ROP, no treatment), and 108 eyes in Group 3 (treated group; anti-VEGF treatment of ROP with ranibizumab, bevacizumab, or aflibercept). The number of eyes with PAR in these groups was 2 (3.7%), 4 (17.4%), and 45 (41.7%), respectively. PAR was detected in 30 of 44 eyes treated with aflibercept. The rate of PAR was higher after aflibercept treatment (68.2%) with statistical significance (p = 0.000). This study showed that the prevalence of PAR differs between anti-VEGF drugs. Patients treated with aflibercept have a higher risk of late complications and should be followed closely.